Factors Affecting Delays in Luwansa Manado Hotel Project - Anjas Handayani; Abid Nur Affani (Journal of World Conference (JWC), 2021)
Building construction in Indonesia from year to year is growing, especially in the construction world. The increasing number of construction service providers in recent times should be offset by cost savings, quality in accordance with standards and also project time management. In Indonesia especially in Manado city there are many hotel developments, one of which is the construction of Hotel Luwansa manado. Acting as the main contractor (Main Contractor) of PT. Recta Construction, as the winner of the tender of the project. The construction of Hotel Luwansa Manado is one of the hotel developments not far from Manado City Beach which has 1 Tower, covering 10 floors, roof top, and 2 basements. At the time of implementation of the project one of the sub contractors had already started the foundation work in July 2019 and should have been completed in October 2019. However, the design of the foundation work on the project retreated to January 2020, due to design changes and resulted in the addition of foundation work at The Luwansa Hotel Project Manado. The method carried out in this study is the collection of data through questionnaires distributed to several respondents. The method of analysis performed is quantitative descriptive. The quantitative approach is research that focuses on hypothesis testing, the data used must be measured, and produce a generalized conclusion. This method uses (analysis tools) inference statistics (inconclusive). This method of analysis aims to describe the delay in construction work of Hotel Luwansa Manado building. From the analysis using the SPSS program there are five dominant variables namely X18 of 0.270,X16 of 0.239,X24 of 0.212,X17 of 0.172,and X27 of 0.104.